(untitled) (European Journal of Behavioral Sciences, 2025)
This study explores the impact of empathy and gratitude on educational outcomes among adolescents at Diksha School, an NGO-run institution in Gurgaon, India serving students from marginalized backgrounds. A quantitative experimental design was employed, involving 69 students from grades 7 to 12. The respondents were further divided into control and experimental groups, with students from grade 7th and 12th being control group participants (N=35) and students in grade 8th and 10th being experimental group participants (N= 34). The participants in the experimental group received a structured intervention called the “Chit system” where students would list down good deeds done by their peers, and the chits directed towards the peer were read in front of the whole class once and aimed at fostering empathy and gratitude. Pre- and post-intervention assessments utilized the Toronto Empathy Questionnaire and the Gratitude Questionnaire–Six Item Form. The data were analyzed using descriptive statistics, paired t-tests, ANOVA, and regression analysis. Results indicated significant increases in both empathy and gratitude scores from pre- to post-test across groups, with the intervention group showing greater improvements in gratitude (p = .007) and a significant interaction between time and group (p = .031), highlighting the effectiveness of the intervention. Empathy scores also rose significantly (p .001), underscoring the value of targeted emotional development programs.The study concludes that integrating empathy and gratitude into educational practice can strengthen both social and emotional outcomes, offering a replicable model for other NGO schools seeking to create supportive, inclusive learning environments for disadvantaged youth.